Assessment of Recipient Characteristics and Blood Product Usage Patterns at the Transfusion Medicine Institute of FBiH in 2023. - Elma Catovic-Baralija (Medicinski glasnik, 2025)
ABSTRACT Aim: This study aimed to assess recipient characteristics and blood product usage patterns at the Transfusion Medicine Institute of Federation of Bosnia and Herzegovina(FB&H) in 2023, focusing on clinic-specific blood requests. Methods: The study was conducted from 1st January to 29th December 2023. Data were collected from the Renovatio information system of the Transfusion Medicine Institute of FB&H. Information about patient age, gender, the clinics requesting blood, and the number and composition of issued blood products were gathered. Results: A total of 27,927 units of blood products were issued for 3,341 patients. The average age of transfused patients was 57.25 years, with a nearly equal distribution of male1.662 (49.75%) and females 1.679 (50.25%). Blood requests came from 28 clinics/hospital department, with the following distribution of blood products: 12,267 units of red blood cells, 6,982 units of platelet products, 8,661 units of fresh frozen plasma, and 17 units of cryoprecipitate. The number of doses issued per patient ranged from 1 to 356. Conclusion: Our findings highlight the importance of assessing transfusion practices and recipient outcomes. It is essential to incorporate clinical parameters, such as hemoglobin levels, to optimize transfusion strategies. Multidisciplinary patient blood management approaches are necessary for ensuring safe and effective transfusions, aimed at achieving appropriate clinical outcomes.
Keywords: blood components; blood transfusion; intraoperative care